Effect of Prandtl Number on Forced Convection in a Two Sided Open Enclosure Using Nanofluid - Parvin, S.; Nasrin, R.; Alim, M. A.; Hossain, N. F. (Journal of Scientific Research, 2012)
Analysis of Prandtl number effect on forced convective flow and thermal field characteristics inside an open cavity with porous wavy isothermal wall using water-CuO nanofluid have been performed numerically. The upper and lower surfaces are of temperature Th. The fluid enters from left and exits from right with initial velocity Ui and temperature Ti. Governing equations are discretized using the Finite Element Method. Simulation is carried out for a range of Prandtl number, Pr (from 1.47 to 8.81) and wave amplitude A (from 0 to 0.15) while Reynolds number, Re =100; Darcy number, Da = 100 and solid volume fraction, = 5%. Results are presented in the form of streamlines, isothermal lines, rate of heat transfer, average temperature of the fluid and velocity at mid-height of the channel for various Pr and A. Increasing Pr and lessening A causes the enhancement of heat transfer rate. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i1.9641 J. Sci. Res. 5 (1), 67-75 (2013)